BST Sensor Application: Programmable Night Lamp With Morning Alarm - Khairunneesa Hanie Othman (Universiti Malaysia Perlis, 2008)
A high potential BST Sensor fabricated at UniMAP’s Clean Room was left unused from any further development even though it has good characteristics. The main aim for this project is to develop an application system prototype entitled “Programmable Night Lamp with Morning Alarm” utilizing this sensor to observe its performance and commercialization potential. Further aim is to investigate BST sensor parameters and its properties. Basically, this project involved development of software and hardware with a concept when combining night lamp and alarm to make a complete system. The system is programmable, small in size and low cost. To build the system, early research and bottomto-up design approaches are taken. PIC16F876, a microcontroller from Microchip is used in this project because it has the processor, peripherals interface and other features in single chip with low power consumption. The sensor itself was tested to gain as many data and characteristics as possible. The input of the system will be the light intensity that determines the output derived by the controller. Sensitivity, optimum range and repeatability have been the major constraint during this project implementation. Therefore,further research and improvement of the sensor are crucial to further develop this system.